Two decades of progress in gastric cancer peritoneal metastasis: a bibliometric perspective on molecular mechanisms and therapeutic innovations - Qian, Jin; Tu, Xiaoxuan; Chen, Jianglin; Chen, Sisi; Zhou, Yi; Sun, Chuan; Wu, Zhibing (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) is the fifth most common malignant tumor worldwide. The peritoneum is a common site of metastasis in advanced GC, and patients with gastric cancer peritoneal metastasis (GCPM) have a very low 5-year survival rate. Systemic therapy has limited efficacy for peritoneal metastases, and early diagnosis is difficult. In this paper, we analyzed the GCPM-related literature by bibliometric methods, aiming to identify the research hotspots and trends and to provide a basis for clinical practice and research planning.MethodsBased on the Web of Science Core Collection database (WoSCC), we screened the GCPM-related literature published from 2004 to 2024. Countries, institutions, authors, journals, and keywords were analyzed and visualized by tools such as CiteSpace, VOSviewer, Scimago Graphica, RStudio, and the Bibliometrix package.ResultA total of 2416 publications were included in this study. The growth rate of GCPM publications is positive until 2021, with a slowdown in the near future. Japan dominated the research output (842 publications), followed by China (748 publications) and the United States (268 publications). Japanese-affiliated organizations and researchers are extremely productive in the field of GCPM. The most frequently cited document was Japanese gastric cancer treatment guidelines 2014 (ver. 4) (citations = 2076). Research focuses on four major clusters: (1) molecular mechanisms of GCPM; (2) prognosis of GCPM; (3) chemotherapy of GCPM; and (4) intraperitoneal treatment of GCPM. Emerging trends include key pathways of GCPM, artificial intelligence (AI) and multi-omics-driven early diagnosis, novel intraperitoneal therapeutic modalities, and immunologic/targeted drugs.ConclusionJapan is a leader in GCPM research. Recently, the focus of GCPM research has shifted from basic treatment to precision and personalized treatment through the integration of molecular mechanisms, novel intraperitoneal therapeutic modalities, and AI technologies. Current challenges include the lack of standardized validation systems for emerging technologies and regional differences in clinical practice. In the future, there is a need to promote global collaborative trials and optimization of multimodality therapy. The results of this study provide a key direction and systematic basis for future exploration of GCPM.